Juridical Review of Stock Investment with Cryptocurrency Investment Which Interests The Investors and Its Legal Protection - Iva Latifah Permana (UNISKA LAW REVIEW, 2022)
Investment is currently a phenomenon that attracts the attention of the public. In addition to stocks, the presence of digital currencies or cryptocurrencies makes investors' interest to invest even higher. Stocks and crypto assets are easy to use in the marketplace. Every investment carries the risk of investors losing their money. Neither the company nor the investors know when the price will rise or fall, so investors need legal protection to prevent losses. This research is legal research with the type of library research. The results of the study show that investing in stocks through the stock exchange and investing in cryptocurrencies in futures exchanges are different investment instruments, which can be seen from their form and implementation. Stock exchanges prevent investors from losing their money in investments, there are minimum and maximum limits on the value of falling prices. Meanwhile, crypto asset investments tend to have more high risk because of their speculative and volatile nature and a very open market, so to protect investors from losses, the government must establish regulations that investors need. Stock investment has been regulated in Act Number 8 of 1995 on the Capital Market and further regulated by Government Regulation and Financial Services Authority Regulation. Crypto assets are regulated in the Regulation of the Minister of Trade of the Republic of Indonesia Number 99 of 2018 on General Policies for the Implementation of Crypto Asset Trading, and there are no specific regulations governing the use of cryptocurrencies in Indonesia.